Reformasi Sistem Hukum Pidana Sebagai Upaya Pemberantasan Tindak Pidana Korupsi - Jafar Sodik (Universitas Janabadra, 2019)
This research aims to analyse and formulate a system of criminal law reform corruption related to the types of criminal acts, criminal sanctions and criminal liability in order to eradicate corruption in the future.This research is a type of normative legal research supported by primary data, descriptive and form of prescriptive. The data used are secondary data consisting of primary, secondary and tertiary legal materials and primary data in the form of interviews. The process of data analysis using qualitative methods,conceptual approach, by analysing the data in the form of interviews, documents, regulations and related theories that produce descriptive-analytical data.The impact of the extraordinary criminal corruption is no longer as national problem but has also become an international problem so there needs to reform the material law in the context of combating corruption.Criminalization of criminal acts of corruption of several acts that need to be criminalized as a criminal act of corruption within UNCAC there are at least four actions: bribery of foreign public officials and officials of public international organizations, trade of influence, illegal enrichment, private bribery and outside UNCAC categorize money laundrying from the proceeds of criminal acts of corruption and crimes essentially constituting corruption but not regulated as a criminal act of corruption such as, cheating during the election. Reforming of material law also needs to be done related to criminal sanctions. Existing criminal sanctions are very less deterrent effect. Some consepts of material criminal law reforming related to criminal sanctions are, first is the separation of arrangements between people and corporations because of nature and nature. Both concepts of criminal sanction double track system. The three system are minimal and maximum special. The three concepts of cumulative criminal sanctions formulation and accountability to corporations that need to be affirmed and explained so that they can be applied and clear and precise formulation of specific subjects in corruption related to public servants, state organizers and law enforcement officers. The renewal of the criminal law of material related to corruption crime should be done immediately to create the concept of prevention of corruption crime that is repressive, preventive and restorative.